The Process of Cultivating Virtue Among Students at the Nuurul Khairaat Islamic Boarding School - Moh. Aldin; Siti Novi Napisah (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2026)
The cultivation of akhlaqul karimah represents a central foundation in Islamic education, particularly within Islamic boarding schools that serve as key institutions for character formation among youth. This study addresses the persistent challenge of students’ difficulties in translating moral values into daily behavior, alongside variations in character education approaches across pesantren contexts. The research aims to describe and evaluate strategies for fostering noble character at Nuurul Khairaat Islamic Boarding School in Rogo Village. A qualitative descriptive-exploratory design was employed, involving the boarding school leader, five teachers, and thirty purposively selected students. Data were collected through two months of participatory observation, in-depth interviews, and documentation analysis. The findings reveal that character development is implemented through integrated strategies, including habituation of daily worship, teacher role modeling, continuous supervision, enforcement of structured regulations, and the study of classical moral texts contextualized with contemporary values. Established in 2020, Nuurul Khairaat Islamic Boarding School demonstrates measurable progress in shaping students’ character. The effectiveness of these strategies is reflected in improved discipline, mutual respect, and the ability of students to internalize and practice moral values in everyday life, even amid digital-era challenges. This study offers a contextual contribution to the development of adaptive moral education models for emerging Islamic boarding schools in Central Sulawesi.